The relationship between the severity of Hypomineralized Second Primary Molar (HSPM) and the severity of Molar Incisor Hypomineralization (MIH). - فرحات نور الدين; نبيه رسلان (Latakia University Journal -Medical Sciences Series, 2023)
Aim of study: To investigate the relationship between the severity of Hypomineralized Second Primary Molar (HSPM) and the severity of Molar Incisor Hypomineralization (MIH). Materials and Methods: A cohort-prospective study was conducted in a sample of (207) randomly selected children aged (4 to 5) years, the second primary molar was examined by intra-oral imaging, after cleaning the teeth, clinical photographs were taken of score (if any) HSPM, and then the sample were evaluated until completing the eruption of the four permanent first molars to investigate the presence of MIH, applying the diagnostic criteria for MIH and HSPM adopted by the European Academy of Pediatric Dentistry. Results: This study showed a significant increase in the prevalence of MIH in the study sample (81%) (168 out of 207) children, The study also showed a statistically significant correlation between the severity of HSPM and MIH, the probability of first permanent molar to have MIH increased with the presence of HSPM, (OR=12.6; CI: ]4.9-31.9[; p-value<0.0001). The study also showed a statistically significant correlation in terms of the number of MIHaffected teeth. Conclusions: There is a correlation between MIHin terms of the severity of the defects (mild, severe), and there is a correlation in the severity of the injury depending on the number of affected teeth at the level of the child, Whereas, the more primary molars affected by HSPM, the greater the likelihood of first permanent molars to develop MIH.